Parents’ System for Developing Bilingual Children in Makassar - Rahayu, Sri; Dollah, Syarifuddin; Atmowardoyo, Haryanto (Celebes Journal of Language Studies, 2023)
This research is a qualitative descriptive study that aims to find out the system used by parents in developing their children to become bilingual in English. There are 2 research questions in this study, namely parents’ system implementation in Makassar in developing their children to be bilingual and the factors that influence the system used by parents in developing their children to be bilingual. The subjects in this study were 5 parents who developed their children to be bilingual and 5 children who were developed to be bilingual by their parents aged 3-5 years. Research data were obtained through in-depth observation and interviews. Data analysis techniques, namely data condensation, data display, and drawing/checking conclusions. Based on data analysis, it was found that there is one system most often used by parents in Makassar, namely Mixed language. It is different with previous research which said that the most parent system used by parents is One Parent One Language (1P1L). It is different because the subjects in previous study are immigrants, while the subject in this research are not immigrants. Then, most of the subject work outside the house, so it is impossible for parents to share two languages. Then, there are 3 factors that influence the system used by parents in developing their children to become bilingual, namely age, media use, and community factors. Based on findings and discussion, it can be concluded that the five parents who were the subjects of this study chose to use the Mixed Language system in the development of bilingual children. Then, the factor that most influences the system used is the media usage factor, especially handphone.